The Relevance of Numbered Heads Together Learning Model to Students' Mathematical Communication Ability Based on Vygotsky's Theory - Nurhidayat, Arif (Sean Institute, 2022)
Numbered Heads Together learning model is a cooperative learning model that aims to improve collaborative mathematical understanding. Mathematical communication ability is the ability to convey ideas or mathematical understanding. NHT can be applied in mathematics learning activities on campus to improve students' mathematical communication skills and is relevant or in accordance with Vygotsky's learning theory which emphasizes collaboration in learning activities. The results of the collaboration of the NHT learning model can improve students' mathematical communication skills because there is a process of social interaction and exchange of ideas in the learning model